2016
DOI: 10.1007/s00605-016-0938-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-inner automorphisms of order p in finite p-groups of coclass 3

Abstract: In this paper we study the existence of at least one noninner automorphism of order p of a non-abelian finite p-group of coclass 3, whenever the prime p = 3.2010 Mathematics Subject Classification. 20D45, 20D15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In 2014, using derivation, Abdollahi et al [1] showed that every p-group of co-class 2 has a non-inner automorphism of order p leaving Z(G) elementwise fixed. Recently, Ruscitti et al [7] confirm the conjecture for finite p-group of co-class 3, with p = 3. Also, it is not very difficult to see that every finite p-group G of maximal class has a non-inner central automorphism of order p that fixes Φ(G) elementwise.…”
mentioning
confidence: 80%
“…In 2014, using derivation, Abdollahi et al [1] showed that every p-group of co-class 2 has a non-inner automorphism of order p leaving Z(G) elementwise fixed. Recently, Ruscitti et al [7] confirm the conjecture for finite p-group of co-class 3, with p = 3. Also, it is not very difficult to see that every finite p-group G of maximal class has a non-inner central automorphism of order p that fixes Φ(G) elementwise.…”
mentioning
confidence: 80%
“…To be more precise, Abdollahi and Ghoraishi in [4] proved that in some cases the non-inner automorphism of order p can be chosen so that it leaves Z(G) elementwise fixed. Finally, Abdollahi et al [5] proved the conjecture for p-groups of coclass 2, and quite recently in [17] M.Ruscitti, L. Legarreta and M.K.Yadav did the same for p-groups of coclass 3 when p is a prime different from 3.…”
Section: Introductionmentioning
confidence: 88%
“…Hence, (20) yields that G admits a non-inner automorphism of order p leaving G p γ 3 (G) elemnetwise fixed, whenever Z 5 (G)∩Z(G p γ 3 (G))…”
Section: By (I)mentioning
confidence: 99%
“…Abdollahi, Ghoraishi, and Wilkens [4] proved the conjecture for finite p-groups of class 3, and Abdollahi et al [5] proved the conjecture for p-groups of coclass 2. Ruscitti et al [20] proved the conjecture for p-groups of coclass 3 with the exception of p = 3. Ghoraishi [10,11] proved the conjecture for groups not satisfying the condition Z * 2 (G) ≤ C G (Z * 2 (G)) = Φ(G), and for an odd order p-group G for which (G, Z(G)) is a Camina pair.…”
Section: Introductionmentioning
confidence: 96%